REPURCHASE INTENTION PADA LAYANAN STREAMING DIGITAL: BAGAIMANA KONTRIBUSI SOCIAL MEDIA MARKETING? - Rahma Khoirunnisa; Usep Suhud; Nofriska Krissanya (PT. Hasba Edukasi Mandiri, 2025)
The digital era has driven the rapid development of social media. Digital streaming service companies view this phenomenon as an opportunity to utilize social media platforms to retain consumers. Consequently, the digital streaming industry faces intense competition, making social media marketing an effective strategy to increase consumers' repurchase intention, particularly through enhancing brand engagement, brand image, and brand awareness. This study aims to analyze the influence of social media marketing on repurchase intention in digital streaming services by examining the roles of brand engagement, brand image, and brand awareness. The research employs a quantitative method, with data collected through an online questionnaire distributed to 265 respondents. Data testing and analysis were conducted using SPSS and Structural Equation Modeling (SEM) based on AMOS. The results show that social media marketing does not have a positive effect on brand engagement but has a positive effect on brand image, brand awareness, and repurchase intention. Moreover, brand engagement does not positively affect repurchase intention, whereas brand image and brand awareness do positively influence repurchase intention. These findings reinforce the importance of social media marketing in building consumer repurchase intention through brand image and brand appeal.